2014
DOI: 10.1111/1758-5899.12187
|View full text |Cite
|
Sign up to set email alerts
|

The Buen Vivir: A Policy to Survive the Anthropocene?

Abstract: This article examines the ideology and the politics of buen vivir as the government of Rafael Correa in Ecuador has implemented them from 2007 to 2013. The analysis focuses on the implications of this model, which is based on a traditional Andean world view. The article first explores the main components of buen vivir including its focus on strengthening democratic participation and environmental justice. Second, the implementation of this ideology is analysed through a review of the new constitution and gover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In this way, the experiences of the good life outlined here align with the kind of vision that underpins buen vivir, with its emphasis on interdependent configurations reflective of community citizenship and sociality as central to wellbeing (Calisto Friant & Langmore, 2015). Participants' relationships are negotiated and strengthened around and within the land, based on the needs and preferences of the actors-human and more-than-human-who live alongside them.…”
Section: Enacting the Interspecies Good Lifementioning
confidence: 83%
See 1 more Smart Citation
“…In this way, the experiences of the good life outlined here align with the kind of vision that underpins buen vivir, with its emphasis on interdependent configurations reflective of community citizenship and sociality as central to wellbeing (Calisto Friant & Langmore, 2015). Participants' relationships are negotiated and strengthened around and within the land, based on the needs and preferences of the actors-human and more-than-human-who live alongside them.…”
Section: Enacting the Interspecies Good Lifementioning
confidence: 83%
“…Our findings reveal transformative multiactor relational configurations in unique landscape contexts (Heley & Jones, 2012; Lobao et al., 2007), while the resulting discussion has considered the implications of this for the politics and practice of sustainability. By drawing on the notion of buen vivir , we have shown that the good life is not individualistically driven but reflects and depends upon communities and the unique environmental situations in which they are embedded (Calisto Friant & Langmore, 2015; Gudynas, 2011, 2013). We have therefore expanded existing research into the understanding and practice of sustainability in rural areas by demonstrating the usefulness of a relational approach and illuminating the central role domestic animals can play in shaping postgrowth lifestyles (Bohme et al., 2022; Hodges, 1999; Houtbeckers, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Ecuador's government captured grassroots and indigenous demands within neoliberal economies and excluded indigenous communities from real democratic debates about land ownership and environmental justice (Alonso González and Vázquez, 2015;Villalba-Eguiluz and Etxano, 2017) This co-optation of the political and cultural proposal of the Sumak Kawsay delinked it from its communitarian roots, its capacity to incorporate plural visions, and its spiritual connection with land and nature (Ferreiro Lago, 2018). In that manner, Ecuador's government captured Sumak Kawsay within a secular, anthropocentric and egocentric perspective, that allows the reproduction of extractivism (Calisto Friant and Langmore, 2015).…”
Section: Overcoming Anthropocentrism: Dialogues Between Subaltern Pos...mentioning
confidence: 99%
“…The postcolonial shift of the late twentieth century increased the visibility of traditionally marginalised communities, questioning who, where, and how knowledge is produced. That opened some opportunities to include non-Western epistemological perspectives in debates about development, ecology, and sustainability, encouraging scientists and policymakers to create intercultural spaces where indigenous and scientific knowledges (Walsh, 2010;Gudynas, 2011;Calisto Friant and Langmore, 2015;Demaria and Kothari, 2017) and practices joint to create better environmental management tools and methods (Briggs, 2013;Watson, 2013;Tengö and others, 2014). However, most of these attempts to create intercultural spaces still use secular and scientific epistemic warrants to validate non-Western knowledges (Mazzocchi, 2018), thus reproducing the hegemonic infrastructure of knowledge production and limiting the epistemic emancipatory potential of these spaces.…”
Section: Introductionmentioning
confidence: 99%
“…The Postcolonial shift of the late XX century and the increasing visibility of traditionally marginalised communities, who questioned who, where and how knowledge is produced, opened a space of opportunity to include non-western epistemological perspectives in debates about development, ecology, and sustainability. This encourages environmental scientist and policymakers to join indigenous knowledge (Walsh 2010;Gudynas 2011;Calisto Friant and Langmore 2015;Demaria and Kothari 2017) and practices as instruments for better environmental management (Briggs 2013;Watson 2013;Tengö et al 2014). However, these attempts to create intercultural spaces still used Western epistemic warrants to validate other knowledges (Mazzocchi 2018), preventing plural and epistemically emancipatory spaces.…”
Section: Introductionmentioning
confidence: 99%